FORMULASI SANKSI TINDAKAN TERHADAP PELAKU PENANGKAPAN IKAN DENGAN MENGGUNAKAN ALAT TANGKAP TERLARANG DI KAWASAN PESISIR - Doni Anggarda Paramitha; Davit Rahmadan; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Fishing with explosives or blast fishing is very rife, especially in coastal areas wherethe main perpetrators are small fishermen. Perpetrators who use prohibited fishing gear, oneof which is the use of explosives, has been regulated in Law No. 45 of 2009 concerningAmendments to Law No. 31 of 2004 concerning Fisheries. In the regulation of sanctions, thelaw only focuses on punishment of perpetrators and there is no regulation of sanctions so thatmarine ecosystems damaged by the actions of perpetrators cannot be repaired again.Therefore, the purpose of this thesis research is first, to describe criminal sanctions againstfishing perpetrators using prohibited fishing gear in the current positive law and theimplementation of the regulation. Second, To formulate the formulation of sanctions foractions needed to be applied to fishing actors using prohibited fishing gear to protect marineecosystems in the future.This research can be classified into normative types of legal research. In this type oflegal research, often the law is conceptualized as what is written in laws and regulations orthe law is conceptualized as rules or norms that are a benchmark for age behavior that isconsidered appropriate. Therefore, the first source of data is only secondary data, consistingof primary legal material, secondary legal material, and tertiary data.This study obtained the first result, namely in the regulation of sanctions againstperpetrators of fishing with prohibited fishing gear, namely the use of explosives which hasbeen regulated in Article 84 paragraph (1) of Law No. 45 of 2009 concerning Amendments toLaw Number 31 of 2004 concerning Fisheries and threatened with a maximum prison sentenceof 6 (six) years and a maximum fine of IDR 1,200,000,000.00 (one billion two hundred millionrupiah). Meanwhile, the crime of blast fishing committed by small fishermen is specificallyregulated in Article 100B of the Fisheries Law. threatened with a maximum imprisonment of1 (one) year or a maximum fine of Rp250,000,000.00 (two hundred fifty million rupiah).However, if we look closely, sanctions arrangements only focus on punishment on perpetratorsand there is no sanction arrangement, sanctions are taken so that marine ecosystems aredamaged as a result of the actions of perpetrators that cannot be repaired. Second, theregulation of criminal sanctions that are relevant for small fishermen who use explosives whenfishing is the renewal of the criminal law by imposing sanctions in an effort to preserve andutilize marine resources so that they run well.Keywords: Action Sanctions, Prohibited Fishing Gear, Sanction formulation